2015
DOI: 10.1109/twc.2015.2415812
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Cross-Layer Protocol Design for Magnetic Induction Communication in Wireless Underground Sensor Networks

Abstract: Wireless underground sensor networks (WUSNs) enable many applications such as underground pipeline monitoring, power grid maintenance, mine disaster prevention, and oil upstream monitoring among many others. While the classical electromagnetic waves do not work well in WUSNs, the magnetic induction (MI) propagation technique provides constant channel conditions via small size of antenna coils in the underground environments. In this paper, instead of adopting currently layered protocols approach, a distributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 30 publications
0
41
0
Order By: Relevance
“…Acoustic technique cannot be used in UG channel due to vibration limitation. In magnetic induction (MI), [18], [25], signal strength decays with inverse cube factor and high data rates are not possible. Moreover, communication cannot take place if sender receiver coils are perpendicular to each other.…”
Section: Related Work Wireless Communication Inmentioning
confidence: 99%
“…Acoustic technique cannot be used in UG channel due to vibration limitation. In magnetic induction (MI), [18], [25], signal strength decays with inverse cube factor and high data rates are not possible. Moreover, communication cannot take place if sender receiver coils are perpendicular to each other.…”
Section: Related Work Wireless Communication Inmentioning
confidence: 99%
“…To date, MI channel has been usually modeled using MI‐Tx and Rx circuits as a whole (Lin et al, ; Sun & Akyildiz, ; ). A novel approach separates the Tx and Rx circuits to better characterize the signal attenuation but considers the media unbounded (Silva & Moghaddam, ).…”
Section: Study Casesmentioning
confidence: 99%
“…Proposed framework performed better than geographical routing and transmitted power level‐based greedy routing with a minimum energy saving of 40% and 8 dB of throughput gain. Lin, Akyildiz, Wang, and Sun expand their work and reported that energy saving can be up to 50% with a 6 dB of throughput gain. In addition, a 2‐phase decision game is developed to determine the best energy savings and throughput gain with a low computation complexity.…”
Section: Packet Size Optimization For Underground Sensor Networkmentioning
confidence: 99%
“…[60][61][62] Similarly, there are a few studies on the packet size optimization for WUSNs. 21,63,64 Lin et al 63 propose a distributed cross-layer optimization framework, Xlayer, that conserves energy with a gain of throughput for magneto-inductive WUSNs that satisfies a predefined level of QoS. Authors compare the performance of Xlayer with current layered protocols in the literature.…”
Section: Packet Size Optimization For Underground Sensor Networkmentioning
confidence: 99%